Mr. Chickee's messy mission - Curtis, Christopher Paul (Wendy Lamb Books, 2007)
Flint Future Detective Club members Steven Carter and his friends Russell and Richelle follow Russell's dog, Rodney Rodent, into a mural to chase a demonic-looking gnome, only to find the mysterious Mr. Chickee on the other side.